The use of physical condition e-module on the shooting accuracy of petangue athletes : A literature review - Tri Putri Apriani; Zulbahri Zulbahri; Kamal Firdaus; Ardo Okilanda (STKIP Singkawang, 2025)
Petanque is a sport that requires a high level of accuracy in shooting to achieve the best results in the match. The physical condition of athletes is an important factor that affects shooting accuracy, so effective training methods are needed to improve athletes' performance. One of the methods that can be applied is the use of e-modules as an interactive learning medium in improving the physical condition of athletes. This study aims to examine the effectiveness of the use of e-modules in improving physical condition and its impact on the shooting accuracy of petanque athletes through literature studies. The research method used is The inclusion criteria for the selected literature focus on studies related to e-modules in sports training, physical conditioning for precision-based sports, and the role of physical fitness in petanque performance. Databases such as Google Scholar, Scopus, ScienceDirect, and PubMed were used to ensure comprehensive data collection. The results of the study show that the use of e-modules as a physical training aid provides significant benefits in improving endurance, strength, and body balance of athletes, which contributes to improving shooting accuracy. In addition, the e-module allows athletes to get more systematic, flexible, and easily accessible training materials at any time. The conclusion of this study is that e-modules can be an effective alternative in learning and training the physical condition of petanque athletes to improve shooting accuracy. Therefore, the integration of e-modules in the petanque training program is recommended as an innovative strategy that can support the development of athletes more optimally